2019
DOI: 10.1109/access.2019.2903487
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Indoor Localization Using Received Signal Strength and Channel State Information

Abstract: Indoor localization has received wide attention recently due to the potential use of wide range of intelligent services. This paper presents a deep learning-based approach for indoor localization by utilizing transmission channel quality metrics, including received signal strength (RSS) and channel state information (CSI). We partition a rectangular room plane into two-dimensional blocks. Each block is regarded as a class, and we formulate the localization as a classification problem. Using RSS and CSI, we dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
105
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(123 citation statements)
references
References 37 publications
0
105
0
Order By: Relevance
“…In the case of non-moving objects, the multipath propagation is different depending on the location or the shape of objects where they exist between antennas. This characteristic is used for location estimation and object identification [6][7][8][9][10] among others. In these applications, the main classification algorithms for estimation, such as SVMs and convolutional neural networks (CNNs), are used.…”
Section: Related Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of non-moving objects, the multipath propagation is different depending on the location or the shape of objects where they exist between antennas. This characteristic is used for location estimation and object identification [6][7][8][9][10] among others. In these applications, the main classification algorithms for estimation, such as SVMs and convolutional neural networks (CNNs), are used.…”
Section: Related Studiesmentioning
confidence: 99%
“…In addition to the two types of eigenvalues, α R x T x ,k and β R x T x ,k , the maximum eigenvalues derived from the variance-covariance matrix composed of the CSI amplitude or the phase CSI phase in Equations (10) and (11) are used. This method to create the maximum eigenvalues is the same as that of [11].…”
Section: Calculation Of Feature Values and Human Flow Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the complexity of DNNs is also important since it affects the computational load and implementation cost of a system. Thus, in this paper we use prediction accuracy and network complexity, presented in our previous work [25], as the metrics for the evaluation and comparison of the deep neural networks. The major contributions of this work are summarized as follows:…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, research often looks into applying remote sensing in this field. It has been shown that indoor localization [6,16,18], measuring physiological signals [11,13,17,20], human identification [2,12], and general human activity recognition/gesture detection [1,7,21,22] are achievable by using CSI. The performances of such systems is comparable to the existing wearable wireless sensor systems.…”
Section: Introductionmentioning
confidence: 99%